La política lexicográfica actual de las academias de la lengua española: el caso del Diccionario de americanismos (ASALE, 2010) - Lauria, Daniela (2017)
This paper analyzes a singular political-linguistic event in the framework of the New panhispánica language policy (RAE y ASALE 2004): the publication of the Dictionary of Americanisms (2010). One glottopolitics perspective that considers dictionaries as interventions in public space of language, noting the relationship they establish with broader historical requirements is adopted. The work under study operates as a complementary gesture of the idea of “global Spanish” which would undermine lexical variants conceived as localisms. That is, both models of language, withemphasis on the global or local as appropriate, different meta-linguisticarguments and discourses, participate in a game denoted by the same economicinterests, eager to capture a more profitable market.